PERTUMBUHAN TEKNOLOGI INFORMASI INDIA PASCA BERGABUNG DENGAN SAFTA (2006-2009) - Iin Mailina Martha; Saiman Pakpahan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
This research explains about the growth of the Information Technlology in India after merged into SAFTA, a free trade area organization for South Asia, since 2006. India exceeded Information Technology want to bring excellence to the global world market.The data sources that is used on this research is which was collected from books, journals, magazines, reports mass media and internet websites. To analyze the case, researcher used the theory of economic integration by Ernest B. Haas the concept on this research is a process where political actors in several national territory compelled different for loyalty, hope and their political activity to a new state center the institute.This research shows that, India became a member of SAFTA, make India is growing rapidly, generating up more than 2,5 million peoples sent to the Information Technology Companies to several America and Europe, than works on India Software Companies in America and Asia.Keywords : India, Technology Information, SAFTA, Economic Integration, National Interest